Ilmu Kimia Tumbuhan Lauraceae Indonesia: X. Alkaloid Benzilisokuinolin Dari Litsea cassiaefolia - Euis Holisotan Hakim; Sjamsul Arifin Achmad; Buchari Buchari; Sidharta Pramutadi (Journal of Mathematical and Fundamental Sciences, 1994)
Penyelidikan kimia telah dilakukan untuk pertama kalinya terhadap tumbuhan Litsea cassiaefolia. Pada penyelidikan ini, melalui kombinasi kromatografi partisi dan cara pemisahan yang lazim, tiga alkaloid telah ditemukan, yakni disentrin (I), dehidrodisentrin (II), dan disentrinon (III), masing-masing termasuk alkaloid benzilisokuinolin jenis aporfin, dehidroaporfin, dan oksoaporfin. Karakterisasi ketiga alkaloid tersebut dilakukan berdasarkan data spektroskopi UV, 1H-NMR, 13C-NMR, dan massa. Di antara ketiga senyawa tersebut, disentrin (I) merupakan alkaloid utama yang ditemukan dengan kadar yang cukup tinggi; oleh karena itu, sifat biologi senyawa ini diselidiki lebih lanjut. Ditemukannya ketiga alkaloid dalam tumbuhan ini sangat berguna sebagai dasar kajian kemotaksonomi. The first chemical study on Litsea cassiaefolia had been carried out in our laboratory. In this investigation, by combination of partition chromatography and common separation methods, three alkaloids had been isolated, namely dicentrine (I), dehydrodicentrine (II), and dicentrinone (III), which belong to benzylisoquinoline alkaloids of the types aporphine, dehydroaporphine, and oxoaporphine, respectively. The characterization of the alkaloids had been based upon the UV, 1H-NMR, 13C-NMR and mass spectroscopic evidence. Among these compounds, dicentrine (I) is the major alkaloid which may be isolated in relatively higher yield, thus, the biological property of this compound is being further investigated. Finding the alkaloids in this plant is beneficial as a basis for chemotaxonomy.